PENGEMBANGAN KREATIFITAS SAMPAH PLASTIK YANG BERNILAI JUAL UNTUK MENDUKUNG PEREKONOMIAN MASYARAKAT VISAR CIBINONG - Dedy Budiyono; Asri Kusuma Wardhani; Dinihari Mulya Lestari (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2025)
Plastic waste is a major problem for Indonesia because it causes environmental pollution. Plastic waste is not very good for the environment because landfills are inadequate, causing uncontrolled waste and making the place a breeding ground for several organisms and animals that can cause disease. such as hepatitis, cancer, and skin diseases, and disposal of plastic waste can cause health problems. Even plastic waste is waste that is difficult to decompose. Plastic waste is processed by reusing and recycling. Training on processing plastic waste by recycling carried out by PKK women is one way to reduce the problem of plastic waste. The aim to be achieved in this research activity is to increase creativity, skills, and training for processing plastic waste. The methods used in this research are the counseling stage and the implementation stage. In this training, materials, and practices for processing plastic waste are provided. into goods that are useful and have economic value.